Headache and Facial Pain in Multiple Sclerosis: A Narrative Review - Lukasz Kolakowski; Katarina Alexandra Ebner; Athina Papadopoulou (Clinical and Translational Neuroscience)
Headache and facial pain syndromes are frequently observed in people with multiple sclerosis (MS), often affecting young adults during pivotal stages of their lives. These conditions can disrupt their ability to work, maintain relationships, and engage in daily activities, leading to significant socio-economic and personal challenges. This narrative review summarizes key epidemiological data and diagnostic insights into headache and facial pain disorders in people with MS. It addresses the complexities of diagnosing these overlapping conditions and highlights specific therapeutic considerations.